Meyer Schapiro's critical debates : art through a modern American mind - O'Donnell, C. Oliver (Charles Oliver), 1983- (The Pennsylvania State University Press, 2019)
"Explores the life, career, and intellectual debates of art historian Meyer Schapiro, who worked at the nexus of artistic and intellectual practice and from there confronted some of the twentieth century's most abiding questions"--